Design strategy and mechanism of nitrite oxidation suppression of elevated loading rate partial nitritation system - Ikem, Juliet; Chen, Huiyu; Delatolla, Robert (Frontiers in Microbiology, 2023)
There is a current need for a low operational intensity, effective and small footprint system to achieve stable partial nitritation for subsequent anammox treatment at mainstream municipal wastewaters. This research identifies a unique design strategy using an elevated total ammonia nitrogen (TAN) surface area loading rate (SALR) of 5 g TAN/m2.d to achieve cost-effective, stable, and elevated rates of partial nitritation in a moving bed biofilm reactor (MBBR) system under mainstream conditions. The elevated loaded partial nitritation MBBR system achieves a TAN surface area removal rate (SARR) of 2.01 ± 0.07 g TAN/m2.d and NO2–N: NH4+-N stoichiometric ratio of 1.15:1, which is appropriate for downstream anammox treatment. The elevated TAN SALR design strategy promotes nitrite-oxidizing bacteria (NOB) activity suppression rather than a reduction in NOB population as the reason for the suppression of nitrite oxidation in the mainstream elevated loaded partial nitritation MBBR system. NOB activity is limited at an elevated TAN SALR likely due to thick biofilm embedding the NOB population and competition for dissolved oxygen (DO) with ammonia-oxidizing bacteria for TAN oxidation to nitrite within the biofilm structure, which ultimately limits the uptake of DO by NOB in the system. Therefore, this design strategy offers a cost-effective and efficient alternative for mainstream partial nitritation MBBR systems at water resource recovery facilities.